Implications of different criteria for percutaneous coronary intervention-related myocardial infarction on study results of three large phase III clinical trials: The CHAMPION experience. Issue 2 (1st March 2018) - Leonardi, Sergio; Lopes, Renato D; Steg, Ph Gabriel; Abnousi, Freddy; Menozzi, Alberto; Prats, Jayne; Mangum, Stacey; Wilson, Matthew; Todd, Meredith; Stone, Gregg W; Gibson, C Michael; Hamm, Christian W; et al.
Abstract: Aims: The purpose of this study was to test whether different results between Cangrelor versus standard therapy to acHieve optimal Management of Platelet InhibitiON (CHAMPION) PCI/PLATFORM and PHOENIX trials are due in part to different definitions of percutaneous coronary intervention (PCI)-related myocardial infarction (MI). Methods and results: In patients with acute coronary syndrome (ACS), the definition of MI was identical in CHAMPION PCI and PLATFORM and did not require an assessment of baseline cardiac biomarker status, while in PHOENIX specific MI criteria were associated with different patient presentations. The same MI criteria were used in PCI, PLATFORM, and PHOENIX for patients with stable angina. Logistic regression assessed the effect of cangrelor on MI (PCI- and non-PCI related) in the combined PCI/PLATFORM population and in PHOENIX. Consistency of cangrelor's effect in PCI/PLATFORM and in PHOENIX in patients with stable angina and in those with an ACS (with or without ST elevation) was evaluated. Overall, the incidence of PCI-related MI at 48 h was 6.3% in PCI/PLATFORM and 4.0% in PHOENIX. In patients with ACS, MI incidence was 6.4% in PCI/PLATFORM and 1.7% in PHOENIX, and 6.3% and 5.6%, respectively in stable angina patients. Cangrelor's effect on PCI-related MI differed between PCI/PLATFORM (odds ratio (OR) 1.03, 95% confidence interval (CI) 0.90–1.17) and PHOENIX (OR 0.80, 95% CI 0.66–0.98) with p INT =0.04. This difference was mostly evident in patients with ACS ( p INT = 0.06) while the effect was consistent in patients with stable angina ( p INT =0.81). Results were similar when all MIs were analyzed. Conclusions: The definition of PCI-related MI has important implications for event rates, treatment effect, and study results. This illustrates the importance of a rigorous assessment of PCI-related MI in clinical trials of patients with an ACS.